Integration and Non-Integration of Life Skills: is There an Influence on the Development of Basketball Shooting Skills? - Tri Prasetyo; Padli; Tjung Hauw Sin; Ronni Yenes; Fiky Zarya; Oki Candra; Ali Munir (Jurnal Pendidikan dan Pengajaran, 2024)
Lack of integration of life skills in training can result in athletes having high technical skills but lacking the ability to adapt and cooperate in everyday life. This study aims to analyze the impact of integration and non-integration of life skills in training on improving shooting skills in basketball. This experimental research was conducted involving 20 basketball players as samples. The collected data will be analyzed using descriptive and inferential statistics. This research uses an independent t-test and ANOVA. The study showed a significant increase in shooting accuracy and technique in the experimental group, which received integrated life skills, compared to the control group. These findings indicate that a holistic training approach that includes aspects of life skills can positively improve technical abilities in basket ball sports. Based on these results, this study recommends that trainers consider integrating life skills into training programs. This supports improving the athlete's technical skills and contributes to a more holistic development of the athlete, which includes aspects of valuable life skills. The implications of this research can help deepen understanding of how the integration of life skills can influence various aspects of sports performance.